A Study of Lognormal Model for Air Pollution Concentration - Bhandari, Prem Sagar (BMC Journal of Scientific Research, 2018)
The Lognormal distribution has been widely used to represent the type of air pollutant concentration distribution. There are different methods to estimate the distribution parameters such as the method of moments, percentiles, maximum likelihood estimation (MLE) and Bayesian method of estimation. In this study, the theoretical distribution Lognormal is used to fit the parent distribution of PM 10 of Putalisadak of Kathmandu, Nepal. Two estimating methods namely method of maximum likelihood and method of moments are used to estimate the parameters of the theoretic distributions.